2010
DOI: 10.1261/rna.2089110
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic shuttling of the La motif-containing protein Sro9 might link its nuclear and cytoplasmic functions

Abstract: Diverse steps in gene expression are tightly coupled. Curiously, the La-motif-containing protein Sro9 has been shown to play a role in transcription and translation. Here, we show that Sro9 interacts with nuclear and cytoplasmic protein complexes involved in gene expression. In addition, Sro9 shuttles between nucleus and cytoplasm and is exported from the nucleus in an mRNA export-dependent manner. Importantly, Sro9 is recruited to transcribed genes. However, whole genome expression analysis shows that loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…The integrity of the TAPtagged and slf1 deletion strain was verified by PCR. The strains SRO9-TAP MEX67 and SRO9-TAP mex67-5 have been described earlier (Rother et al 2010). Strains SLF1-TAP MEX67 (MATa;15;112; trp1-1; SLF1-TAPTTRP1-KL, mex67THIS3; pUN100-MEX67) and 15;112; trp1-1; SLF1-TAPTTRP1-KL, mex67THIS3; pUN100-mex67-5) were obtained by integration of the TAP-tag at the C-terminal end of the SLF1 ORF into the genome of the MEX67 shuffle strain by homologous recombination (Puig et al 2001).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The integrity of the TAPtagged and slf1 deletion strain was verified by PCR. The strains SRO9-TAP MEX67 and SRO9-TAP mex67-5 have been described earlier (Rother et al 2010). Strains SLF1-TAP MEX67 (MATa;15;112; trp1-1; SLF1-TAPTTRP1-KL, mex67THIS3; pUN100-MEX67) and 15;112; trp1-1; SLF1-TAPTTRP1-KL, mex67THIS3; pUN100-mex67-5) were obtained by integration of the TAP-tag at the C-terminal end of the SLF1 ORF into the genome of the MEX67 shuffle strain by homologous recombination (Puig et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The Slf1p paralog Sro9p is implicated in both transcription and translation (Sobel and Wolin 1999;Tan et al 2000) and has recently been shown to shuttle between the nucleus and the cytoplasm (Rother et al 2010). In order to elucidate the mode of Slf1p-mediated mRNA expression regulation, we first investigated the cellular localization of Slf1p under normal growth conditions and after inhibition of mRNA export, a condition in which Sro9p was shown to accumulate in the nucleus (Rother et al 2010). Slf1 was TAP-tagged in WT and isogenic mex67-5 cells, bearing a temperaturesensitive mutant allele of the mRNA export factor Mex67, which is thought to be the primary mRNA export factor in yeast.…”
Section: Slf1p Is Localized To the Cytoplasm And Affects The Decay Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The ChIP experiments were performed as in Rother et al (2010), and the ChIP-chip experiments were performed as in Meinel et al (2013). RPC25 and rpc25-S100P cells were grown for 10 h at 25°C or shifted to 37°C.…”
Section: Generation Of a Nab2 Temperature-sensitive Allelementioning
confidence: 99%